Photo-induced SI-ATRP for the synthesis of photoclickable intercalated clay nanofillers. Issue 92 (19th September 2016) - Vo, V.-S.; Mahouche-Chergui, S.; Babinot, J.; Nguyen, V.-H.; Naili, S.; Carbonnier, B.
Abstract : Design of functional and hairy nanoclay intercalated assemblies using tandem photoinduced surface initiated ATRP-1, 3 dipolar cycloaddition/thiol-yne click reactions. Abstract : In situ photoinduced SI-ATRP is reported as a novel and efficient route for preparing intercalated nano-clay fillers bearing clickable functions. Poly(propargyl methacrylate) chains are grown inside the clay interlayer after silanisation and grafting of bromine ATRP initiator. The generic clickable character is demonstrated through grafting with azidomethyl benzene and mercaptosuccinic acid via photodriven 1, 3-dipolar cycloaddition and thiol-yne click reactions, respectively.